Rediscovery and supplemental description of Paris birmanica (Melanthiaceae), a species endemic to Myanmar - Yang, Jun; Yang, Xue-Fei; Oo, Thaung-Naing; Wang, Yue-Hu; Li, Heng (Phytotaxa, 2019)
Paris Linnaeus (1753: 367) comprises 30 species of perennial herbs, distributed in Eurasia, and the center of distribution is the Himalayan-Hengduan Mountion area (Li et al. 1998, Osaloo & Kawano 1999, Liang & Soukup 2000, Li et al. 2017, Ji et al. 2017, Wang et al. 2017, Yang et al. 2018, Liu et al. 2018). Many are medicinal plants. Paris birmanica, described in Daiswa by Takhtajan (1983), was transferred to Paris by Li & Noltie (1997). It was also noted (Li et al. 1997, Li et al. 1998) that P. birmanica is endemic to Myanmar. However, since the type specimens were collected in the 1920s, P. birmanica had not been sighted by botanists, which left the morphological characteristics of this species without detailed description of its rhizome, ovary and ovules.